Micro-processes of moral normative engagement with CSR tensions: the role of spirituality in justification work - Shin, Hyemi (Journal of business ethics, 2022)
Although CSR scholarship has highlighted how tensions in CSR implementation are negotiated, little is known about its normative and moral dimension at a micro-level. Drawing upon the economies of worth framework, we explore how spirituality influences the negotiation of CSR tensions at an individual level, and what types of justification work they engage in when experiencing tensions. Our analysis of semi-structured interview data from individuals who described themselves as Buddhist and were in charge of CSR implementations for their organizations shows that spirituality influences how they compromise among competing moral values by identifying two forms of justification work: compartmentalizing work and contextualizing work, which help spiritual practitioners minimize moral dissonance.